2012 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2012
DOI: 10.1109/icassp.2012.6287910
|View full text |Cite
|
Sign up to set email alerts
|

Singer verification: Singer model .vs. song model

Abstract: This paper proposes a method to verify the singer identity of a given song. The query song is modeled as a GMM learned on the features extracted from sustained sung notes of the song. Each note is described by the shape its spectral envelope and by the temporal variations in frequency and amplitude of its fundamental frequency. The singer identity is verified with two approaches: the model of the query song is compared to a singer-based GMM or compared to the GMM of another song performed by the same singer. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There is no efficient algorithm which works fine on speech identification and singing voice characterization together. So information on the singer's voice is essential to organize, extract, and classify music collections [5]. Sometimes, a viewer is interested to hear Indian video songs based on their interest like favorite playback singer, actor, and actress.…”
Section: Introductionmentioning
confidence: 99%
“…There is no efficient algorithm which works fine on speech identification and singing voice characterization together. So information on the singer's voice is essential to organize, extract, and classify music collections [5]. Sometimes, a viewer is interested to hear Indian video songs based on their interest like favorite playback singer, actor, and actress.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous papers have reported that these dynamic components strongly affect singing-voice perception, and that the former relates to the naturalness and individuality of a singing voice while the latter relates to singing styles and skills [4]. Accordingly, extracting these components from a raw F 0 contour automatically can be potentially very beneficial for any singing voice applications, such as singer identification, singing skill evaluation and the synthesis of more natural and varied singing voices [5,6,7].…”
Section: Introductionmentioning
confidence: 99%